Identification of candidate genes for drought tolerance in soybean through QTL mapping and gene expression analysis - Park, Gi-Rim; Bae, Seon-Hwa; Kang, Beom-Kyu; Seo, Jeong-Hyun; Oh, Jae-Hyeon (Frontiers in Genetics, 2025)
IntroductionDrought stress significantly reduces soybean yield, underscoring the need to develop drought-resistant varieties and identify the underlying genetic mechanisms. However, the specific genes and pathways contributing to drought tolerance remain poorly understood. This study aimed to identify candidate genes associated with drought tolerance in soybean using a recombinant inbred line (RIL) population derived from PI416937 and Cheongsang.MethodsA quantitative trait loci (QTL) mapping study using a 180K high-quality SNP array and composite interval mapping on 140 recombinant inbred lines, coupled with RNA sequencing of treated and control groups, was conducted to identify candidate genes for drought tolerance in soybean.Results and DiscussionThrough QTL mapping and differential gene expression profiling, five candidate genes were identified, with two (Glyma.06G076100 and Glyma.10G029600) highlighted as putative candidates based on functional annotations. These genes appear to play critical roles in stress tolerance, including ion homeostasis and the regulation of plasma membrane ATPase, as well as the synthesis of heat shock proteins (HSPs) that mitigate dehydration and thermal stress. These findings advance our understanding of the genetic basis of drought tolerance in soybean and provide valuable targets for breeding programs aimed at developing resilient cultivars.